The Role of Nursing and Respiratory Therapy Teams in Managing Respiratory Disorders: A Multidisciplinary Approach - Alsaedi , Madawi Hassan; Aldossari, Waad Salman; Majrashi, Wejdan Hassan; Almagrby, Sara Mohmmad; Hazazi, Zainab Ali; Aldossari , Ziad Eid; Fahad, Manal Hassan; B.Hawsawi , Hissah Mohammed; Alqahtani, Mishal (Journal of Ecohumanism, 2024)
The management of respiratory disorders requires a collaborative, multidisciplinary approach to ensure optimal patient outcomes. Nurses and respiratory therapists play pivotal roles in addressing the complex needs of patients with conditions such as asthma, chronic obstructive pulmonary disease (COPD), and acute respiratory distress syndrome (ARDS). This article explores the complementary roles of these healthcare professionals, emphasizing the importance of effective communication, shared decision-making, and coordinated care strategies. By leveraging their unique skills and expertise, nursing and respiratory therapy teams can deliver comprehensive care that improves clinical outcomes, reduces complications, and enhances patient satisfaction. Challenges in collaboration, such as role ambiguity and communication barriers, are also addressed alongside proposed strategies for overcoming them. The article concludes by highlighting future opportunities for interdisciplinary research and the integration of advanced technologies to further improve respiratory care.